Implementation of the Principal's Religious Leadership in Building Student Character at MI Rouhotul Ulum, West Jakarta - Zahra, Siti Ervina; Japar, M.; Karnati, Neti (PT. BATARI EDU CALYA, 2024)
Education is an institution that plays an important role in forming character apart from family. Character formation in educational institutions is usually carried out at school. One way that can be done to shape student character is through religion, starting from the religious leadership of the school principal which is carried out at MI Roudhotul Ulum, Kalideres District, West Jakarta. This research aims to find out in depth the principal's religious leadership implemented in the school and see the character displayed by the students. This research used qualitative methods with informants such as the Deputy Principal, Teacher Council, Administrative Staff and several students which was carried out in December 2023. Data collection techniques used in this research included observation, interviews and documentation methods. Meanwhile, the data analysis technique used is the Milles and Hubberman method which uses three methods, namely data reduction, data presentation and data verification. The result of this research is that there is a tahlil activity which is held regularly every Friday, led by grade 6 students with the hope that the religious character will be better embedded in the students and will be more beneficial to society.